Pengaruh Profitabilitas dan Leverage Terhadap Tax Avoidance dengan Ukuran Perusahaan sebagai Moderasi pada Sektor Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022 - Nugraha, Dicky Bachtiar; Utaminingtyas, Tri Hesti; Respati, Dwi Kismayanti (LPPM Universitas Negeri Jakarta, 2023)
Every company is expected to pay out taxes in accordance with the laws that have been rooted by the government regarding earnings. On the other hand, there are a number of organizational structures that do not adhere to the need that they pay taxes as a matter of law. The objective of this study is to investigate the connection between profitability and debt in the context of companies avoiding tax payments. A wide variety of energy-related companies are included in this study, which listed on the Indonesia Stock Exchange between the years 2018 and 2022. During the course of the sample collection, which was carried out using the approach of purposive sampling, a total of 170 data were observed. Utilizing SPSS Version 26, which was built for the purpose of this study, the application of the interaction model of moderated regression analysis was carried out on the data that was gathered for this investigation. Therefore, these models are easier to comprehend due to the fact that this is the case. It has been shown via statistical analysis that there is no connection between tax avoidance and earnings. It is possible that the size of the company will have an impact on the use of leverage to avoid paying taxes. Nevertheless, the size of the company does not have any bearing on the use of profitability for the purpose of tax avoidance. The results of this research prove that previous research is still inconsistent and grand theory can still be used as a basis for developing hypotheses.